Using game-based learning to teach orthopaedics to perioperative nurses: A real game changer - Lesy, Rachelle (Operating Room Nurses Association of Canada Journal, 2025)
Nursing shortages have been evident in perioperative nursing and healthcare organizations are adapting education to train more perioperative nurses in a timelier fashion. Many educators are blending online theory courses with hands-on learning, such as game-based learning (GBL) to combat this issue. Game-based learning can come in various forms, such as escape rooms, simulation games, and virtual reality, which accommodate the multi-generational, interprofessional culture of the perioperative setting. The use of GBL in the perioperative environment has been found to increase staff engagement, foster teamwork, enhance knowledge retention, and improve problem-solving and technical skills. This literature review explores the application of GBL techniques in the surgical specialty of orthopedics. Perioperative nursing in orthopedics presents unique challenges, such as complex instrumentation, high surgical demands, and low staff engagement. By incorporating GBL techniques into orthopedic perioperative education, perioperative nurses could improve their knowledge retention, enhance their technical skills, and improve teamwork.